Design of atomic force microscope cantilevers for combined thermomechanical writing and thermal reading in array operation - CROSS, GRAHAM (IEEE, 2002)
In thermomechanical data writing, a resistively-heated atomic force microscope (AFM) cantilever tip forms indentations in a thin polymer film. The same cantilever operates as a thermal proximity sensor to detect the presence of previously written data bits. This paper uses recent progress in thermal analysis of the writing and reading modes to develop new cantilever designs for increased speed, sensitivity, and reduced power consumption in both writing and reading operation. Measurements of cantilever electrical resistance during heating reveals physical limits of cantilever writing and reading, and verifies a finite-difference thermal and electrical simulation of cantilever operation. This work proposes two new cantilever designs that correspond to fabrication technology benchmarks. Simulations predict that the proposed cantilevers have a higher data rate and are more sensitive than the present cantilever. The various cantilever designs offer single-bit writing times of 0.2 ?s-25 ?s for driving voltages of 2-25 V. The thermal reading ?R/R sensitivity is as high as 4?10-4 per vertical nm in near steady-state operation.
PUBLISHED
Keywords: Physics